"Nationalizing" Details in the Comedy of Hamza "The Tricks of Maysary" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article shows by means of dialogues the image of Maisara, which occupies an important place in Hamza's work, and the aphoristic characteristic of the proverb in his speech, the elegance-rejection inherent in the anecdote, the manifestation of lyricism inherent in the song. It is suggested that the ‘nationalising’ details in Maisara's speech indicate that she is a very clever, resourceful, eloquent woman and is capable of solving many problems.